A Radiographic Assessment of Dental Morbidity in Patients with Multiple Myeloma Undergoing Autologous Stem Cell Transplant: A Retrospective Study. Issue 1 (May 2021) - Wazzan, Taggreed; Jagtap, Rohan; Mona, Mahmoud; Katz, Joseph
Aim: To assess the dental and oral morbidity in multiple myeloma patients as expressed in dental radiographs before autologous stem cell transplant. Materials and Methods: A retrospective study involving 79 multiple myeloma patients was designed to collect data prior to their autologous stem cell transplant. Patients were seen at the oral medicine clinic at the University of Florida College of Dentistry during the years 2010–2013. Through available patient data and interpretation of radiographs, the following variables were recorded: age, gender, carious lesions, periodontal disease, and periapical radiolucency. In addition, the incidence of root fragment retention and the presence of punched-out osteolytic lesions were recorded. Cochran–Mantel–Haenszel (CMH) tests and logistic regression were performed for descriptive analysis and presentation of the data. Results: Seventy-nine multiple myeloma patients were recruited for this study. Ages ranged from 28 to 79 years (mean = 61, SD = 9.6), including 41 (51.9%) females and 38 (48.1%) males. The results demonstrated dental decay in 64.56% of patients, periodontal disease in 62.03%, apical rarefying osteitis in 13.92% of patients, and punched-out lesions in 24.05% of patients. Conclusion: Our study indicates high dental morbidity in multiple myeloma patients prior to autologous stem cell transplant. The elimination of foci of infection is highly recommended prior to autologous stem cell transplant for this high-risk population because of the potential risk of bacteremia/septicemia from oral bacteria associated with dental morbidity.